Utilization of Spices, Seasonings, and Food Colorings by the Malay Tribe in Pontianak City - Januariza, Putri; Afandi, Afandi; Pramulya, Muhammad (Universitas Tanjungpura, 2025)
The use of plants as spices, seasonings, and food colorings has been an important part of traditional Malay cuisine and beverages in Pontianak City. However, the influx of modern culture and the increasing use of instant ingredients have caused local knowledge regarding the use of these plants to gradually decline. This study aims to determine the types of plants used and their parts in traditional Malay cuisine in Pontianak City. This study used a qualitative approach with descriptive methods. Data were obtained through observation, documentation, and interviews with cooks and spice and spice traders. The results showed that there are 25 plant species used by the community, consisting of 11 types of spice plants, 11 types of herbs, and 4 types of natural food coloring plants. Each plant has a specific function based on the part used, such as rhizomes, leaves, fruits, seeds, and bark. These findings illustrate that traditional knowledge regarding plant utilization is still maintained through inheritance from generation to generation, both orally and directly in daily cooking practices. The diversity of plants used not only enriches the flavor and color of dishes but also reflects the local wisdom of the Malay community in Pontianak City in preserving culinary culture. Efforts to preserve this knowledge are important considering its great potential as a source of learning biology based on local wisdom and its contribution to understanding biodiversity in the surrounding environment.